Morfologia das glândulas salivares maiores de cutias (Dasyprocta aguti Linnaeus, 1766) - Oliveira Júnior, Carlos Magno (2014)
Studies on wild animal morphology serve as the theoretical basis for the management and conservation of different species, because they provide the necessary information for the implementation of measures which help in the keeping of these animals in captivity, in their natural habitat or even in the reintroduction to the original habitat. Studies about the morphology of cutias approach the various systems, but not a single study makes reference to both topography and structure arrangement of their salivary glands. Thus, this work sought to macro and microscopically describe the larger salivary glands of cutias. Ten adult animals were utilized to develop the methods related to the macroscopic aspect of the glands itself, as well as light microscopy, electronic transmission microscopy and electronic scanning microscopy. Four larger salivary glands were identified in the studied animals: parotid glands, submandibular glands, zygomatic glands and sublingual glands. The glands presented themselves as being tubulo-acinar, containing ducts of extremely varied sizes in their parenchyma. With the exception of the parotid glands, which were strictly serous, the others were mixed. In the same manner, only the submandibular glands bore grainy ducts. The cutias exposed four pairs of larger salivary glands; these animals may fulfill the needs of a model for studies concerning the undergone anatomical changes made by rodents to adapt to the various habitats of the planet